2009
DOI: 10.2527/jas.2007-0717
|View full text |Cite
|
Sign up to set email alerts
|

Influence of source and concentrations of dietary fiber on in vivo nitrogen excretion pathways in pigs as reflected by in vitro fermentation and nitrogen incorporation by fecal bacteria123

Abstract: The inclusion of dietary fiber (DF) in diets has been suggested as a way to reduce NH(3) emission in pig barns because it contributes to a shift in N excretion from urine to feces owing to enhanced bacterial growth in the intestines. This study compared an in vitro method to measure bacterial protein synthesis during fermentation with an in vivo N excretion shift induced by diets differing in DF concentrations and solubility. The first experiment measured the effect of graded concentrations of sugar beet pulp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
62
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 24 publications
(37 reference statements)
11
62
0
Order By: Relevance
“…The results of that study are published elsewhere (Jha et al, 2011b). Previous studies (Canh et al, 1997;Zervas and Zijlstra, 2002;Bindelle et al, 2009) have shown that the inclusion of isolated DF in pig diet shifts N from urine to faeces, which leads to reduced N excretion in the environment. This study assumed that it is also true when DFs are in their natural matrix as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of that study are published elsewhere (Jha et al, 2011b). Previous studies (Canh et al, 1997;Zervas and Zijlstra, 2002;Bindelle et al, 2009) have shown that the inclusion of isolated DF in pig diet shifts N from urine to faeces, which leads to reduced N excretion in the environment. This study assumed that it is also true when DFs are in their natural matrix as well.…”
Section: Discussionmentioning
confidence: 99%
“…However, inclusion of fermentable DF (Awati et al, 2006) and reduction of protein (Htoo et al, 2007) in weanling diets reduces protein fermentation along the gastrointestinal tract. Moreover, the presence of fermentable DF in the diet can also reduce the emission of gaseous nitrogenous compounds by shifting N excretion from urine to faeces (Canh et al, 1997;Zervas and Zijlstra, 2002;Bindelle et al, 2009), thus reducing the NH 3 emission from piggery (Mroz et al, 2000;Nahm, 2003). O'Connell et al (2006) found increased urinary N and decreased faecal N when pigs were fed with barley-based fibre-rich diet, with significant interaction between protein levels, fibre source and enzyme supplementation on NH 3 emission.…”
Section: Introductionmentioning
confidence: 99%
“…This was an unexpected finding as the majority of in vitro fermentation studies allow pigs to adapt to the diets for 7 to 14 days (Bauer et al, 2004;Anguita et al, 2006;Awati et al, 2006;Bindelle et al, 2009;Martín-Peláez et al, 2009). Thus, animals in the HL-treatment might have also not been fully adapted on day 1 of the actual experiment, after consuming silage for 3 weeks in the pre-experimental period.…”
Section: Discussionmentioning
confidence: 97%
“…In this type of in vitro fermentation studies, faecal donor animals are fed a well-defined diet in order to obtain a standardised microbial community. For many in vitro fermentation studies involving pigs, a dietary adaptation time of 7 to 14 days is routinely used when a new diet is implemented (Bauer et al, 2004;Anguita et al, 2006;Bindelle et al, 2009;Martín-Peláez et al, 2009). Interestingly, there is a general lack of information on the time required for the large intestinal microbiota to adapt to the diet fed to the pigs for these in vitro fermentation studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, low faecal-N-digestibility values not always mean low protein value. High fermentable fibre content of some forage species decreases the faecal apparent digestibility of N through a shift in N excretion from urinary-N (urea) to faecal-N (bacterial protein) without systematically altering the protein value of the diet (Bindelle et al, 2009). Therefore, the only actual protein value should mention ileal digestibility or possibly the standardised ileal digestible (SID) AAs of the forage ingredients, as these values might strongly differ from raw AA composition (Tables 2 and 4).…”
Section: Chemical Composition and Variabilitymentioning
confidence: 99%